Health Risk Assessment of Some Toxic Metals for Skin Whitening Creams in Iraqi Markets - Al-ansari, Raghad F.; Jabir, Maryam H.; Kadhum, Hussam H.; Sulaiman, Ghassan M. (Iraqi Journal of Science, 2025)
White skin has long been considered the standard of beauty; however, women who use skin-whitening creams may be unaware that these products contain toxic metals, posing significant health risks to consumers. Therefore, this research aimed to detect the concentration of some toxic metals in thirty whitening creams by flame atomic absorption spectroscopy and to evaluate the carcinogenic and non-carcinogenic risks for all tested samples. The results showed that the average concentrations for all samples were in the order Cd < Co < Cr < Ni < Hg < Pb. All samples exhibited elevated concentrations of Hg, reaching levels up to ten times higher than the permissible limits set by the World Health Organization (WHO) and three times according to the Europe Union (Eu), and Canada. Non−carcinogenic risk results for the current study showed that the hazard quotient (HQ) and hazard index (HI), for all samples were <1. While, carcinogenic risks for Cd, Cr, Ni, and Pb were within the permissible limits, which indicates no harmful health effects, and consumers are safer using the product, but daily exposure can lead to accumulation that may cause cancer.